(untitled) (Research, Society and Development, 2022)
Background: Futsal is one of the most popular sport in Brazil with millions of players worldwide. It is characterized by intermittent stimuli of high intensity anaerobic actions. Recently, studies have shown that imagery resistance training (IRT), like conventional strength training, can increase muscle strength, making it reasonable to think that this effect can also be transferred to muscle power. Purposes: we aimed to verify the acute responses of IRT on muscle power in teenage Futsal players. Methods: fifteen Futsal athletes were enrolled and underwent three visits to the laboratory: 1) familiarization with the resistance exercise they would undergo; 2) one them for vertical jump test after the IRT session and the other one for control session, without any intervention before vertical jump test. Sessions 2 and 3 being applied in random order. Results: the results indicate that acute IRT improved muscle performance, since it produced higher power output [3134.5 Watts (2744 - 3796.3)] than control session [2952.4 Watts (2637.55 - 3433.45)] (Z=3.4078; p=0.0007). In addition, all participants in IRT group showed some improvement after the IRT session. Conclusions: a single imagery resistance exercise session can increase acute muscle power output in teenage Futsal athletes.